EFEKTIVITAS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK PADA PEMBELAJARAN MATEMATIKA - adisty arisma utami (LPD IKIP PGRI Pontianak, 2023)
Realistic Mathematics Education (PMR) is an approach to mathematicseducation adopted from Realistic Mathematics Education (RME) which has beendeveloped in the Netherlands since 1970. PMR tends to provide explanations related torealistic things, so that students can easily digest the learning delivered by educators .This study aims to conduct a literature review related to the effectiveness of realisticmathematics education (PMR) in learning mathematics. The research method chosen inthis study is the SLR (Systematic Literature Review) method. Data collection was carriedout by documenting and reviewing all articles related to mathematics education in theperiod 2010 –2020. The articles used in this study were 30 accredited national andinternational journal articles obtained from Google Schoolar, Research Gate, SINTA,DOAJ, and Scopus. Based on this research, it was found that Realistic MathematicsEducation (PMR) is able to improve learning outcomes and can improve many students'mathematical abilities. Starting from the ability of intuition, mathematical problemsolving ability, connection and communication skills of students. Keywords: Realistic Mathematics Education, Mathematics Learning, Systematicliterature Review